Hepatic oxidative stress in ovariectomized transgenic mice expressing the hepatitis C virus polyprotein is augmented through suppression of adenosine monophosphate‐activated protein kinase/proliferator‐activated receptor gamma co‐activator 1 alpha signaling. Issue 10 (14th November 2013) - Tomiyama, Yasuyuki; Nishina, Sohji; Hara, Yuichi; Kawase, Tomoya; Hino, Keisuke
<x xml:space="preserve">Abstract</x> Aim Oxidative stress plays an important role in hepatocarcinogenesis of hepatitis C virus (HCV)‐related chronic liver diseases. Despite the evidence of an increased proportion of females among elderly patients with HCV‐related hepatocellular carcinoma (HCC), it remains unknown whether HCV augments hepatic oxidative stress in postmenopausal women. The aim of this study was to determine whether oxidative stress was augmented in ovariectomized (OVX) transgenic mice expressing the HCV polyprotein and to investigate its underlying mechanisms. Methods OVX and sham‐operated female transgenic mice expressing the HCV polyprotein and non‐transgenic littermates were assessed for the production of reactive oxygen species (ROS), expression of inflammatory cytokines and antioxidant potential in the liver. Results Compared with OVX non‐transgenic mice, OVX transgenic mice showed marked hepatic steatosis and ROS production without increased induction of inflammatory cytokines, but there was no increase in ROS‐detoxifying enzymes such as superoxide dismutase 2 and glutathione peroxidase 1. In accordance with these results, OVX transgenic mice showed less activation of peroxisome proliferator‐activated receptor‐γ co‐activator‐1α (PGC‐1α), which is required for the induction of ROS‐detoxifying enzymes, and no activation of adenosine monophosphate‐activated protein kinase‐α (AMPKα), which regulates the activity of PGC‐1α. Conclusion Our study demonstrated that hepatic oxidative stress was augmented in OVX transgenic mice expressing the HCV polyprotein by attenuation of antioxidant potential through inhibition of AMPK/PGC‐1α signaling. These results may account in part for the mechanisms by which HCV‐infected women are at high risk for HCC development when some period has passed after menopause.